Hihiing the sweet spot-workbook - Forhini, Compbell (Chicago: Copy-Workshop, 1992)
Los temas principales de este texto son: Sec 1-The sweet sport, Why hitting the sweet spot works, you already know more than you think, Sec 2- How to find the sweet spot, learn to read yourself, laying the foundation, Sec 3- Form insight to inspiration, mapping out perceptions, segmenting people, Sec 4- Consumer insight at work, the account planning revolution, the role of the account planner
Incluye bibliografía
Keywords: Mercado al Consumidor; Publicidad